2016
DOI: 10.1177/0269215516652446
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory muscle strength training and neuromuscular electrical stimulation in subacute dysphagic stroke patients: a randomized controlled trial

Abstract: Adding IEMT to SST was an effective, feasible, and safe approach that improved respiratory muscle strength. Both IEMT and NMES were associated with improvement in pharyngeal swallowing security signs at the end of the intervention, but the effect did not persist at 3-month follow-up and no differences in respiratory complications were detected between treatment groups and controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
166
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(169 citation statements)
references
References 33 publications
1
166
1
1
Order By: Relevance
“…Of the four studies that did look at long‐term follow‐up, two found no long‐term effect at 12 weeks (Terre and Mearin , Guillen‐Sola et al . ) and two found a lasting effect: Sun et al . () found sustained benefit at 24 months post‐treatment (in a ‘preliminary case series’) and Lee et al .…”
Section: Discussionmentioning
confidence: 97%
“…Of the four studies that did look at long‐term follow‐up, two found no long‐term effect at 12 weeks (Terre and Mearin , Guillen‐Sola et al . ) and two found a lasting effect: Sun et al . () found sustained benefit at 24 months post‐treatment (in a ‘preliminary case series’) and Lee et al .…”
Section: Discussionmentioning
confidence: 97%
“…The 17 included trials involved 616 participants and investigated the effects of 5 modalities of interventions delivered to improve respiratory function after stroke. Eleven trials compared experimental interventions versus no intervention, 14,16,[25][26][27][28][29][30][31][32][33] 3 compared to sham interventions, [34][35][36] and 3 of the studies compared 2 different modalities of respiratory interventions. [37][38][39] The characteristics of the included trials are summarized in Table 1.…”
Section: Characteristics Of the Included Trialsmentioning
confidence: 99%
“…13 These variables have been commonly used to reflect respiratory function and evaluate the effectiveness of various types of interventions in people with stroke. [14][15][16] Neuromuscular electrical stimulation, 14 transcranial magnetic stimulation, 15 breathing exercises (breathing/chest expansion/diaphragmatic exercises), 16 and respiratory muscle training 6 are examples of applied interventions, which have the potential to improve respiratory function. These interventions may increase the strength and endurance of the respiratory muscles, speed of contractions and power outputs, diaphragm thickness, and lung volumes and flows.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations